Increased levels of plasma IL-1b and BDNF can predict resistant depression patients - Uint,Luciana (2019)
SUMMARY BACKGROUND: There is no strong evidence on the link between inflammatory profile and pattern of drug treatment response in depressive patients that could result in Coronary Artery Disease occurrence. OBJECTIVE: This study aimed to compare the subclinical atherosclerosis markers, inflammatory profile, and BDNF production in Resistant Depression (RD) or Bipolar Affective Disorder (BAD) patients under conventional treatment. METHODS: The population evaluated was comprised of 34 RD, 43 BAD, and 41 controls. Subclinical atherosclerosis markers were evaluated using ultrasonography, tomography, and exercise stress test. Plasma concentrations of TNFα, IL-1β, IL-6, and BDNF were measured using Luminex100™. The usCRP concentration was measured using turbidimetric immunoassay. IL1B, IL6, and TNFA expression were determined using TaqMan®. For the statistical analysis, the significance level was established at p<0.05. RESULTS: Concerning subclinical atherosclerosis markers, only O2 consumption was reduced in the BAD group (p = 0.001). Although no differences were found in gene expression, BDNF and IL-1β plasma concentration was increased in the RD group (p = 0.002 and p = 0.005, respectively) even with an antidepressant treatment, which suggests that these drugs have no effect in IL-1β secretion and that the inflammasome may play a role in therapy response. CONCLUSION: Taken together, both BDNF and IL-1β plasma concentrations could be used to the early identification of RD patients.